Neural networks in fisheries research - Suryanarayana, Iragavarapu; Braibanti, Antonio; Sambasiva Rao, Rupenaguntla; Ramam, Veluri Anantha; Sudarsan, Duvvuri; Nageswara Rao, Gollapalli (Fisheries research, 2008)
Piscimetrics deals with software implementation of experimental design, second-generation artificial intelligence tools, viz. Neural Nets (NNs), genetic algorithms, Fuzzy Logic, Expert Systems, Wavelets and Image analysis in the field of fisheries. A brief sketch of NNs is followed by a review of their applications in forecasting, classification, distribution and fisheries management since 1978. Forecasting in fisheries covers distribution of eggs, recruitment, fish growth/age, biomass and fish catch. Other major areas are identification, abundance and food products, environmental factors and collapse of fishery industry. The data structures are given in tensorial notation. The need for the paradigm shift from classical to multi-level hybrid NNs is emphasized.